(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this study was to find out the effectiveness of using storytelling techniques to improve the speaking skills of eighth grade students at SMP Kartika Wirabuana XX-2 Makassar. The design of this research is pre-experimental. The population of this study were all students of class VIII students of SMP Kartika Wirabuana XX-2. Academic year 2022/2023. Researchers used purposive sampling in determining the sample. VIII grade students consisting of 30 students are the sample in this study. The instrument used to collect data in this study was a speaking test. The data analysis technique used is descriptive analysis with the help of SPSS 24.0. The results of the data analysis showed that there were differences in the mean scores between the pre-test and post-test. The pre- test value was 57.52 and the post-test value was 74.34. There is an increase in the average value of 16,828. The results of the paired sample test are t test = 10,909 and t table is 2,048. The results of the t test are higher than the t table. Thus it can be concluded that Ha is accepted and Ho is rejected. Based on the results of this analysis, it shows that the use of storytelling techniques in speaking skills has an influence on increasing mastery and speaking skills of class VIII students of SMP Kartika Wirabuana XX-2 Makassar 2022-2023.